Innovative Use of Nanomaterials in Treating Retinopathy of Prematurity - Kevin Y. Wu; Xingao C. Wang; Maude Anderson; Simon D. Tran (MDPI AG, 2024)
Background/Objectives: Retinopathy of prematurity (ROP) is a severe condition primarily affecting premature infants with a gestational age (GA) of 30 weeks or less and a birth weight (BW) of 1500 g or less. The objective of this review is to examine the risk factors, pathogenesis, and current treatments for ROP, such as cryotherapy, laser photocoagulation, and anti-VEGF therapy, while exploring the limitations of these approaches. Additionally, this review evaluates emerging nanotherapeutic strategies to address these challenges, aiming to improve ROP management. Methods: A comprehensive literature review was conducted to gather data on the pathogenesis, traditional treatment methods, and novel nanotherapeutic approaches for ROP. This included assessing the efficacy and safety profiles of cryotherapy, laser treatment, anti-VEGF therapy, and nanotherapies currently under investigation. Results: Traditional treatments, while effective in reducing disease progression, exhibit limitations, including long-term complications, tissue damage, and systemic side effects. Nanotherapeutic approaches, on the other hand, have shown potential in offering targeted drug delivery with reduced systemic toxicity, improved ocular drug penetration, and sustained release, which could decrease the frequency of treatments and enhance therapeutic outcomes. Conclusions: Nanotherapies represent a promising advancement in ROP treatment, offering safer and more effective management strategies. These innovations could address the limitations of traditional therapies, reducing complications and improving outcomes for premature infants affected by ROP. Further research is needed to confirm their efficacy and safety in clinical practice.